2019
DOI: 10.1017/jfm.2018.928
|View full text |Cite
|
Sign up to set email alerts
|

Is spontaneous generation of coherent baroclinic flows possible?

Abstract: Geophysical turbulence is observed to self-organize into large-scale flows such as zonal jets and coherent vortices. Previous studies on barotropic beta-plane turbulence, a simple model that retains the basic self-organization dynamics, have shown that coherent flows emerge out of a background of homogeneous turbulence as a bifurcation when the turbulence intensity increases and the emergence of large scale flows has been attributed to a new type of collective, symmetry breaking instability of the statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
(87 reference statements)
1
3
0
Order By: Relevance
“…flows/jets are just emerging with τ e /τ m → 0 (the exactly opposite limit of Bouchet et al (2013)). This perturbative-level agreement is reported by Constantinou et al (2014a); Ioannou (2013a, 2014) for barotropic flows, by Bakas and Ioannou (2018) for baroclinic flows, by Fitzgerald and Farrell (2018a) for vertically sheared stratified flows, by Constantinou and Parker (2018) for magnetized flows in astrophysical settings, and by for the formation of spanwise varying mean flows and mean vortices (streaks-rolls) in 3D channel flows. The reason that the S3T second-order closure works well even for very weak mean flows should be attributed to the existence of the collective flow-forming instability which seems to overpower the disruptive eddyeddy nonlinear interactions, as long as the turbulent intensity is not exceptionally strong (which in most physical situations is usually the case).…”
Section: Introductionsupporting
confidence: 77%
“…flows/jets are just emerging with τ e /τ m → 0 (the exactly opposite limit of Bouchet et al (2013)). This perturbative-level agreement is reported by Constantinou et al (2014a); Ioannou (2013a, 2014) for barotropic flows, by Bakas and Ioannou (2018) for baroclinic flows, by Fitzgerald and Farrell (2018a) for vertically sheared stratified flows, by Constantinou and Parker (2018) for magnetized flows in astrophysical settings, and by for the formation of spanwise varying mean flows and mean vortices (streaks-rolls) in 3D channel flows. The reason that the S3T second-order closure works well even for very weak mean flows should be attributed to the existence of the collective flow-forming instability which seems to overpower the disruptive eddyeddy nonlinear interactions, as long as the turbulent intensity is not exceptionally strong (which in most physical situations is usually the case).…”
Section: Introductionsupporting
confidence: 77%
“…The manifestation of this instability is the emergence of coherent structures in the turbulent flow. It has been shown that the eigenvectors separate into purely barotropic modes with H = 0 and baroclinic modes with Z = 0 [3]. It was also shown in the same work that the eigenvalues for the barotropic (σ ψ ) and the baroclinic (σ θ ) modes, respectively, satisfy the equations:…”
Section: Investigation Of the Eddy-mean Flow Feedbackmentioning
confidence: 76%
“…One such model of the baroclinic stably stratified atmosphere is the Phillips two-layer model on a beta-plane with turbulence sustained by random stirring. Numerical simulations of this model have shown that coherent zonal jets and westward-propagating Rossby waves suddenly emerge from the background of the homogeneous turbulent field when a threshold of the energy rate of the stochastic forcing is surpassed [3]. Interestingly, the emerging structures were found to be barotropic for a strong enough stratification, even in cases of mainly exciting baroclinic eddies.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation